Technologies for the Storage of Hydrogen. Part 1: Hydrogen Storage in its Narrower Sense - Müller, Karsten (Chemie Ingenieur Technik, 2019)
The efficient and dense storage of hydrogen still is a challenge for research and development. Next to compression and liquefaction, there are a number of alternative approaches, which try to enhance storage density by bonding hydrogen to another substance. Physisorbing as well as chemisorbing organic and inorganic carrier systems are possible. Many of these technologies have not yet exceeded the technology readiness level of lab-scale tests. However, some of the technologies have already reached significantly higher technological levels. The first part of this study discusses storage approaches with recovery of elemental hydrogen.
CRIS-Team WoS Importer:2019-04-09